Model of Field Electron Emission from the Edge of Flat Graphene into Vacuum - N. A. Poklonski; A. I. Siahlo; S. A. Vyrko; S. V. Ratkevich; A. T. Vlassov (Приборы и методы измерений)
Graphene-based nanostructures are the promising materials for applications as electron emitters.The aim of the work is to study the field electron emission from the edge of a single graphene plane.In the semi-classical approximation, a model of field electron emission from the edge of a rectangular graphene sheet has been developed.The current density of field electron emission into vacuum from the edge of a flat graphene sheet was calculated depending on the magnitude of the pulling electric field strength.The analysis and comparison of limiting emission currents from graphene and from bulk systems have been carried out.The results of the work can be used in the development of graphene-based field effect cathodes.